Implementation of the Economic Values of Prophet Muhammad in Community Empowerment through the Islamic Financial System - Hussain, Mujahid; Baloch, Shaheena (Help: Journal of Community Service, 2025)
This study aimed to apply the economic values of Prophet Muhammad to strengthen community empowerment through the Islamic financial system. The program emphasized ethical financial literacy, interest-free microfinance, and the integration of Zakat and Sadaqah into productive use as a means to achieve social justice and sustainable development. A participatory action research approach was implemented in a Muslim rural community. Activities included workshops on Islamic economic ethics, the establishment of a Qard Hasan (interest-free loan) fund, and coordination of Zakat and Sadaqah distribution for small business support. Data were collected through observation, interviews, and focus group discussions with community members and leaders. Three main findings emerged. (1) Islamic financial literacy and ethical awareness significantly improved, leading to behavioral transformation in financial practices. (2) The Qard Hasan fund effectively supported local microenterprises and achieved a repayment rate above 90%, creating a sustainable cycle of empowerment. (3) The integration of charitable funds for productive purposes enhanced social solidarity, trust, and cooperation within the community. The findings reveal that the practical application of Prophetic economic values can bridge moral principles with real economic empowerment. However, challenges included limited institutional partnerships and short observation periods. These limitations suggest the need for broader implementation and longer-term evaluation. Implementing Islamic financial ethics through community-based mechanisms provides an effective framework for social transformation and inclusive development. Future research should explore long-term impacts, digital financial applications, and cross-community comparisons to strengthen the global relevance of Prophetic economic models.